Positive climate feedbacks of soil microbial communities in a semi‐arid grassland. (16th November 2012) - Nie, Ming; Pendall, Elise; Bell, Colin; Gasch, Caley K.; Raut, Swastika; Tamang, Shanker; Wallenstein, Matthew D.; Thrall, Peter
Abstract Soil microbial communities may be able to rapidly respond to changing environments in ways that change community structure and functioning, which could affect climate–carbon feedbacks. However, detecting microbial feedbacks to elevated CO2 (eCO2) or warming is hampered by concurrent changes in substrate availability and plant responses. Whether microbial communities can persistently feed back to climate change is still unknown. We overcame this problem by collecting microbial inocula at subfreezing conditions under eCO2 and warming treatments in a semi‐arid grassland field experiment. The inoculant was incubated in a sterilised soil medium at constant conditions for 30 days. Microbes from eCO2 exhibited an increased ability to decompose soil organic matter (SOM) compared with those from ambient CO2 plots, and microbes from warmed plots exhibited increased thermal sensitivity for respiration. Microbes from the combined eCO2 and warming plots had consistently enhanced microbial decomposition activity and thermal sensitivity. These persistent positive feedbacks of soil microbial communities to eCO2 and warming may therefore stimulate soil C loss.